Coronavírus canino (ccov): isolamento e detecção molecular em amostras clínicas - Vieira, Flávia Volpato [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Until now, the disease caused by the canine coronavirus (CCoV) was not fully elucidated, the CCoV role in the pathogenesis of the illness is not quite established. Only after the SARS (Severe Acute Respiratory Syndrome) appearance in human beings caused by a coronavirus in 2002, isolated of a wild mammal, many studies were developed with coronavirus of different species in search of circulating variants. Few studies had reported the presence of CCoV and his variability's in Brazil. Viral enteritis are responsible by high morbidity taxes and mortality in the small animals clinic and, although there are several etiologic agents described, the CCoV and the CPV are not yet considered a major cause of acute gastroenteritis pathogens in young dogs. For the present study, were collected 100 stool samples from dogs attended in a veterinary hospital routine with clinical signs of gastroenteritis (hemorrhagic or not). The CCoV and CPV RNA were amplified in the tested samples. Some of the by-products from the CPV amplification were purified, sequenced, aligned and subjected to the GenBank for the detection of CPV-2c and characterization of CCoV. The CCoV was present in 6% of the analyzed samples, while CPV-2a was identified in 43% of samples and CPV-2b in 18% of the total. A sample pool submitted to the sequencing and filogenetic analysis identified the CPV-2c, reveling that the new variant is already present in Araçatuba - SP. The phylogenetic analyses for CCoV revealed that the studied samples belong to the Subtype CCoV-IIa (pantropic), strengthening the agent identification importance in the canine population, once that the actual available vaccines don't have the new variants so that the dogs from Brazil are susceptible to severe outbreaks, as described in other countries.
Keywords: Cães; Diarreia em animais; Gastroenterite; Parvovirose; Reação em cadeia da polimerase; Coronavírus; Molecular detection